Invariant NKT cells are more abundant in peanut-allergic adults and a subset of CD8+ iNKT cells are depleted after peanut oil exposure - Hopkins, Georgina V.; Cochrane, Stella; Onion, David; Fairclough, Lucy C. (Frontiers in Immunology, 2023)
Introduction: Peanut allergy is one of the most prevalent food allergies globally. Currently, most research into the mechanisms involved in protein allergy focuses on the protein allergens under investigation, and information on the function of accompanying compounds, such as lipids, is scarce. Thus, this research investigates the role of peanut-associated lipids and invariant natural killer T (iNKT) cells in peanut allergy using a novel, human, in vitro assay. Methods: PBMCs from non-allergic and peanut-allergic subjects were stimulated with the glycolipid, α-Galactosylceramide (α-GalCer), over 14 days for iNKT cell expansion. Autologous dendritic cells (DCs) were stimulated with either peanut oil, the lipid-binding peanut allergen, Ara h 8, or both peanut oil and Ara h 8. The expanded iNKT cells were then immunomagnetically isolated and co-cultured for 5 h with autologous DCs, and cytokine expression was measured by flow cytometry. Results: A 5-fold higher iNKT cell population was observed in peanut-allergic subject peripheral blood compared to non-allergic controls. In all subjects, conventional flow analysis highlighted iNKTs co-cultured with autologous α-GalCer-pulsed DCs displayed increased IL-4 and IFN-y secretion within 5 hours of co-culture. A 10-parameter unsupervised clustering analysis of iNKT phenotype found significantly more CD3+CD8+CD25+IL-4+IL-5+IL-10+IFNγ+ cells in non-allergic adults following culture with peanut oil. Conclusion: For the first time, we show iNKT cells are more abundant in peanut-allergic adults compared to non-allergic adults, and peanut lipid-exposed iNKT cells resulted in the identification of a subset of CD8+ iNKT cells which was significantly lower in peanut-allergic adults. Thus, this study proposes a role for iNKT cells and peanut allergen-associated lipids in peanut allergy.